Overview of optical technology for aerosols characterization - Scagliotti, Ariel Fabricio (2022)
The study of the optical properties of particles in micro and macro environments is a field that collects valuable information on the chemistry and microphysics of aerosols (referring to particles and gases). Constant improvements in instrument and detector designs and mechanisms enable measurements with ever-increasing precision and resolution. Moreover, in recent years low-cost open-source technology has emerged as a massive offer, with very good features, which has allowed low-income laboratories and institutions to carry out their own optical measurements on samples and systems of different natures. This review aims to present the main current advances in optical measurements of air samples using optical properties. Emphasis is placed on low-cost technology and its characterization and applications due to its current boom and mass marketing, with the added value of new scientific articles showing advances in its uses and applications. On the one hand, the theory behind spectral photometric measurements is described, and on the other, the bases for detection from the scattering of a coherent light beam. Finally, the main advances in the literature making use of these phenomena are described, complemented with general results of own measurements. In order to focus the analysis, these aspects are presented based on atmospheric measurements.